Fetal Vesicoallantoic Cyst and Intraabdominal Defects: An Unusual Case and Review of the Literature - Mathieu Delvaux; Yves Sznajer; Etienne Marbaix; Jean Marc Biard; Corinne Hubinont; Dandan Shi (Maternal-Fetal Medicine)
Abstract. We present an unusual and, until now, unreported case of vesicoallantoic cyst associated with multiple malformations in a fetus. A differential diagnosis is discussed, including the hypothesis of a genetic disorder.